2000
DOI: 10.2307/3236801
|View full text |Cite
|
Sign up to set email alerts
|

Landscape and species‐level distribution of morphological and life history traits in a temperate woodland flora

Abstract: Abstract. We developed a description of a central New England deciduous hardwood forest based on the distribution within the community of morphological and life history traits (N= 34) and environmental factors. Classification by TWINSPAN of 186 species based on morphological and life history traits identified six major functional groups of species largely corresponding to growth form. A data matrix of plots x traits was ordinated using PCA. Each of the resulting four PCA axes was associated with a major envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
4
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 79 publications
4
35
4
2
Order By: Relevance
“…In those classifications, drainage is sometimes used to characterize plant communities. However, when considering only the berry species used by Black Bears in those classifications, conclusions are equally variable as those in our study (Whitney 1991;Carter et al 1999;Motzkin et al 1999;Mabry et al 2000). Mabry et al (2000) even identified some morphological traits of berry species that are linked with a dry or humid drainage.…”
Section: Influence Of Vertical and Oblique Drainage On The Abundance contrasting
confidence: 39%
See 3 more Smart Citations
“…In those classifications, drainage is sometimes used to characterize plant communities. However, when considering only the berry species used by Black Bears in those classifications, conclusions are equally variable as those in our study (Whitney 1991;Carter et al 1999;Motzkin et al 1999;Mabry et al 2000). Mabry et al (2000) even identified some morphological traits of berry species that are linked with a dry or humid drainage.…”
Section: Influence Of Vertical and Oblique Drainage On The Abundance contrasting
confidence: 39%
“…However, when considering only the berry species used by Black Bears in those classifications, conclusions are equally variable as those in our study (Whitney 1991;Carter et al 1999;Motzkin et al 1999;Mabry et al 2000). Mabry et al (2000) even identified some morphological traits of berry species that are linked with a dry or humid drainage. The results of Motzkin et al (1999) were quite variable, showing that the best predictor of the presence of some berry species is sometimes drainage, sometimes the kind of land use, sometimes the soil quality, or sometimes the presence of natural dis turbances.…”
Section: Influence Of Vertical and Oblique Drainage On The Abundance contrasting
confidence: 39%
See 2 more Smart Citations
“…Nagaike, A. Hayashi Nagaike [31] showed that the species composition, which is characterized by differences in life form and seed dispersal types, clearly differed between broad-leaved secondary forest and Larix kaempferi plantations. Type of life form and seed dispersal are thought to be ecologically important traits in response to disturbance [4,11,26]. In an Appalachian hardwood forest, the herbaceous component of the herb layer was significantly greater in young clear-cut stands than in mature stands, whereas the woody component of the herb layer was significantly greater in mature stands [9].…”
mentioning
confidence: 99%